AN EARTHQUAKE CATALOG OF MID-ATLANTIC RIDGE - Teza, E.; Scordilis, E.M.; Papazachos, C.B.; Karakaisis, G.F. (Bulletin of the Geological Society of Greece, 2016)
The Mid-Atlantic Ridge (M-AR), which runs along the centre of the Atlantic Ocean, is one of the best known divergent boundaries. Seismic studies have been a crucial factor in deciphering the structure of the oceanic crust. For their performance a necessary prerequisite is the compilation of a reliable earthquake catalog of the broader area. In this study, an attempt was made to create an earthquake catalog of M-AR that could become a useful “tool” for large-scale seismological studies of this region. For this reason a very large sample of data from several seismological centers, as well as from already published catalogs of strong earthquakes, was collected and examined. ISC was considered as the main reference agency, while as reference magnitude scale the moment magnitude scale, MW was adopted. The main goal was to identify and organize the best and most recent information available for earthquakes falling within the time window 1900-2014 and the space window bounded by the extended coordinates ~ 81 (N) to -51 (S) and 10 (E) to ~ -50 (W). After magnitude homogenization, check of focal depths and definition of completeness magnitude, a reliable and homogeneous earthquake catalog of M AR consisting of 14,211 events was created, available for any seismological use and further study.